Clinical outcomes following surgical mitral valve plasty or replacement in patients with infectious endocarditis: A meta-analysis - Wang, Song; Zhou, Ting; Bian, Jinhui; Li, Geng; Zhang, Wenjing; Chen, Si; Jiang, Yefan (Frontiers in Surgery, 2023)
Background: The clinical outcome of mitral valve repair (MVP) is considerably more favorable than that of mitral valve replacement (MVR) in patients with degenerative mitral disease. However, the advantages of MVP in patients with infectious endocarditis (IE) have still not been definitely proven. The aim of this meta-analysis was thus to evaluate the suitability of MVP in patients with IE. Considering the difference between active and healed phase, we not only compared the result of patients with IE, but also identified the subgroup with active IE. Methods: A comparison of clinical outcomes of MVP and MVR in patients with IE was performed based on clinical trial data. Relevant articles published from January 1, 2000 until March 18, 2021 were identified in Pubmed and Cochrane Library. Studies with Newcastle–Ottawa Scale (NOS) score less than 6 or lacking of direct comparisons between MVP and MVR were excluded. Hazard ratios (HR) and odds ratios (OR) were used to summary the results. Results: A total of 23 studies with 25615 patients were included in the analysis. The MVP group displayed lower early and long-term mortality, and fewer adverse events. However, this patient group required more reoperations compared with the MVR group. And the reinfection rate is close. Similar results were observed after identifying active IE subgroup, but no statistically significant difference was identified in in the freedom from reoperation due to all-events. Conclusions: Although limitimations exited in this study, MVP and MVR are still beneficial for patients with IE. For skilled surgeons, MVP can be performed for some suitable patients with IE even for patients during active phase.